Kiwa-kiwa handbook for community animators. (Basic Christian Communities-Community Organizing, Philippines, 1991)
This handbook is intended to guide community workers in bringing educative workshops to barrios. It gives step by step encouraging adaptations and creates initiatives. It also uses thought-provoking drawings that uses humor and wit.